Sentence Repetition Task as a Measure to Detect Developmental Language Disorder in Persian - Mohammad Majid Oryadi-Zanjani; Pardis Yari; Zahra Kalkateh (Shiraz University of Medical Sciences, 2022)
Background Developmental language disorder (DLD) is a common disorder in childhood. The aim of this study was to investigate the performance of Persian-speaking children on sentence repetition task (SRT) as a measure to detect DLD.MethodsAs a cross-sectional and observational study, seven 5-to-7-year-old Persian-speaking children with DLD and thirty normal peers were studied using the Persian version of test of language development (TOLD-P: 3) as a diagnostic test and SRT. Finally, the performance of two groups on the SRT was compared by statistical tests at the significance level of 0.05.ResultsThe score of SRT between the children suspected to have DLD and their normal peers were significantly different (P<0.05). Indeed, there was a significant difference between the groups in terms of the mean scores of prepositions (P<0.01), conjunctions (P<0.01), plural case (P<0.01), subject-verb agreement (P<0.05), and word order (P<0.05).ConclusionThe SRT can be used as a promising measure for early detection and intervention of Persian-speaking children with DLD.